Doing research in school: Physics inquiry in the zone of proximal development. Issue 8 (27th April 2016) - Kapon, Shulamit
Abstract: Research experience is increasingly considered an important component of science education at the secondary school and undergraduate levels. This paper presents a case study of students learning in a unique apprenticeship model in which students are engaged in long‐term (18 month) open‐ended research projects in physics that are done at the laboratory in school, and in which the project advisor is a physics teacher supported by a community of teacher–researchers. The goals of the study were to characterize what the students learned, how they perceived their inquiry and their role in it, the features of mentorship they received and the social‐infrastructure in which they and their advisor functioned. Qualitative data were collected over a whole school year through interviews, weekly observations, and content analysis of the final research reports. Participants were the focus advisor, and some of his former and current project mentees. Data on the larger educational context were collected from other project advisors and their mentees. The study documented students' learning gains such as learning of scientific content and skills, internalization of scientific habits of thought as well as developing passion, interest, and agency with regard to science. It documented features of students' engagement that reflect deep involvement in the technical and epistemic aspects of the inquiry, and highlighted the specific features of mentorship, and the social infrastructure that fostered this learning and engagement. It concluded with a theoretical examination of the interaction between a cultural discipline (i.e., physics), the social infrastructure in which the advisor and the students function, the advisor's mentorship style, and the students' learning and engagement. Theoretical and practical implications are discussed. © 2016 Wiley Periodicals, Inc. J Res Sci Teach 53: 1172–1197, 2016